Nova estratégia de abordagem da anemia : aplicação em três localidades de diferentes regiões brasileiras - Costa, Juliana Teixeira (2011)
To describe a new strategy for management of anemia among children and adolescents using hemoglobin portable, low-cost equipment for not only diagnosis but also as a tool for monitoring and strengthening of those responsible for drug treatment. This uncontrolled intervention study was conducted from August 2007 to November 2008 in three different communities: Ilhabela (Sao Paulo), Santa Luzia do Itanhém (Sergipe) and riverside communities of the Amazon (Pará and Amapá). Subjects were assessed for body mass index (BMI) and hemoglobin concentration, hemoglobin using portable Agabê ® in their school environment. Those diagnosed as anemic were treated with ferrous sulfate and evaluated following 12 weeks, with an intermediate consultation after six weeks of treatment. We examined 1408 subjects, 667 in Ilhabela, 219 and 522 in Santa Luzia in the Amazon. A prevalence of 25.6% of anemia in Ilhabela, 22.4% in Santa Luzia do Itanhém and 37.9% in the Amazon. The hemoglobin concentration showed a gradual increase with age. The prevalence of anemia in this population peaked in the age groups of 5 and 6 years. The recovery rate of anemia was 76% in Ilhabela, 79.6% in Santa Luzia do Itanhém and 57.1% in the Amazon. The different methodology, performing the screening in middle school and consultation in the presence of the caregiver in order to timely detect the problem and increase adherence to treatment was effective, giving as final result a high rate of recovery anemic status.